Poverty-Insecurity Nexus: An Albatross to National Development in Nigeria - Oyigebe, Peter Luke; Meshach, Zhizhi R. (Kashere Journal of Politics and International Relations, 2023)
The twin problem of poverty and insecurity in Nigeria has become so pervasive that both government and citizens are overwhelmed. This situation has contributed to the deepening conditions of the people in the midst of plenty, with the attendant effects on national development. Thus, this paper examines the nexus between poverty and insecurity and the effects on sustainable national development in Nigeria, hinging on the frustration-aggression and relative deprivation theories as frameworks of analysis. In doing this, the paper employs the qualitative content analysis approach and relies mainly on secondary sources of data such as textbooks, journal articles, periodicals, conferences papers and the internet, etc. However, the paper reveals that a plethora of factors such as corruption, bad governance and policy inconsistencies have led to majority of the citizenry wallowing in abject poverty culminating to the blazing level of insecurity characterizing the Nigerian state in recent years. Notwithstanding, the paper recommends some far-reaching strategies or measures of addressing poverty and insecurity challenges, including good governance, sectorial and institutional reforms, effective policy and programme formulation and implementation relating to poverty and security in Nigeria.